Role of antiretroviral therapy exposure host genetics on cytomegalovirus infection status and association with gut microbiome profiles among pregnant black African women - Mhandire, Doreen Zvipo (Department of Clinical Laboratory Sciences, 2021)
Cytomegalovirus (CMV) is an important antenatal infection that is prevalent in the developing world. The disabling and potentially fatal effects of CMV acquisition or reactivation during pregnancy on the developing foetus and or neonate are known but, factors predisposing pregnant women to CMV are not well studied. CMV has a wide host cell tropism that includes gut epithelial cells. CMV infection in the gut epithelial cells results in a leaky gut and potential gut microbial dysbiosis. In this study, we set out to determine the prevalence of CMV infection as well as factors associated with CMV reactivation in a cohort of pregnant Zimbabwean women. We also aimed to determine the role of CMV infection and CMV susceptibility host genetics on gut bacterial profiles. Seroprevalence of CMV was determined using the enzyme-linked immunosorbent assay. A high prevalence of previous exposure to CMV, as denoted by the presence of anti-CMV IgG antibodies in participants' sera, was observed. Anti-CMV IgM antibodies that denote active CMV infection were detected in the sera of 4.6% (n=35/524) study participants. Prevalence of CMV was also determined using real time PCR, CMV reactivation was higher (6.7%) when using PCR than when using immunological assays (4.6%). The presence of CMV DNA was significantly associated with HIV positivity (p=0.04). PCR is the gold standard for CMV diagnosis, thus, CMV DNA positivity was used to denote CMV infection status in this thesis. The second objective was to determine if the differential effect of CMV acquisition or reactivation among HIV infected participants was due to variability in plasma efavirenz containing antiretroviral therapy (ART) exposure. Efavirenz (EFV) plasma concentrations were determined using high performance liquid chromatography (HPLC). Single nucleotide polymorphisms (SNPs) in the CYP2B6 gene, which encodes the main EFV metabolizing enzyme were genotyped. Carriers of CYP2B6 poor metaboliser (PM) genotypes (c.516T/T and c.983T/C) had significantly higher mean plasma EFV concentration compared to carriers of CYP2B6 fast metabolizer genotypes (i.e., c.516G/G and c.983T/T). CYP2B6 PM genotype carriers were significantly less likely to be positive for CMV DNA when compared with fast metabolizer genotype carriers (pC (p=0.002), TLR7 rs179008A>C (pC (p=0.003). In contrast, presence of the IL6 rs10499563T>C polymorphism was inversely correlated with CMV infection (p=0.002). The reported genetic variants are reported to modulate proteins involved in immune responses against viral infections, thus, their association with susceptibility to CMV infection. Such findings may assist in the designing of a muchneeded candidate CMV vaccine. Lastly, we set out to determine the possible role of CMV infection in shaping gut microbiota profiles. We report on a significant difference (p=0.001) in the beta diversity of gut bacterial profiles between HIV- and age-matched CMV-infected (cases) and CMVuninfected (controls) participants. Using linear discriminant analysis (LDA) effect size (LefSe), significant differences in the relative abundance of specific bacterial taxa were observed between cases and controls (p2). Significantly lower abundance of Lactobacillus reuteri and Roseburia, genera associated with lower microbial translocation was observed in cases than controls. Lower relative abundance of Lactobacillus and Roseburia, is consistent with microbial translocation and heightened inflammation, respectively, hence higher likelihood of microbial translocation and inflammation occurring in cases than controls. Furthermore, Prevotella copri, a species that has been association with cytokine release and chronic inflammation was significantly more abundant in cases than controls. CMV is a known chronic inflammatory condition, and this study provides further confirmation through the higher relative abundance of P.copri in cases than controls. Biomarker identification has proven to be a successful means of translating molecular data into clinical practice, such as vaccine development in the case of CMV infection. Overall, this study reports the possible interaction of various host factors in facilitating CMV acquisition or reactivation during pregnancy. In the setting of HIV-CMV coinfection, our findings emphasise on the need for genotype guided drug dosage to achieve therapeutic EFV so as to maintain the balance between host and coinfecting microbes in HIV management. Comprehensive genotype guided drug dosage, if taken as a once-off test should be affordable especially in resource-limited settings. This is particularly important in pregnant women who are at a risk of vertically transmitting infection to the immunologically immature foetus and or neonate. Data from this study may assist in curbing the host associated challenges in designing an effective CMV vaccine. Moreover, the biomarkers reported may assist in diagnosis and management of potential CMV acquisition or reactivation during pregnancy. However, bigger prospective, functional studies would be needed to confirm the exact roles of the biomarkers identified in this study in the diagnosis, prognosis and therapeutics of CMV infection.